2003
DOI: 10.1210/en.2003-0570
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin-4 Receptor Messenger Ribonucleic Acid Expression in Rat Cardiorespiratory, Musculoskeletal, and Integumentary Systems

Abstract: We determined melanocortin-4 receptor (MC4-R) mRNA ontogeny in the rat using in situ hybridization and a rat MC4-R riboprobe and showed numerous peripheral sites of expression for MC4-R. The developing heart showed MC4-R mRNA expression as early as embryonic day (E) 14. In the lungs of E16-E20 fetuses, the cells surrounding developing bronchi expressed relatively strong in situ signal. Muscles associated with the respiratory system such as diaphragm and intercostal muscle expressed MC4-R mRNA as early as E14. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 59 publications
4
35
0
1
Order By: Relevance
“…Absence of salt sensitivity in MC4R (Ϫ/Ϫ) mice suggests that renal MC4R, if present in mice kidneys, does not protect against salt sensitivity of blood pressure. Mountjoy et al 36 reported only mild expression of MC4R in the adult rat kidney, and there have been no studies to our knowledge on renal MC4R expression in mice.…”
Section: Effect Of Hsd (4% Nacl) On Cardiovascular Function In Mc4r (mentioning
confidence: 95%
“…Absence of salt sensitivity in MC4R (Ϫ/Ϫ) mice suggests that renal MC4R, if present in mice kidneys, does not protect against salt sensitivity of blood pressure. Mountjoy et al 36 reported only mild expression of MC4R in the adult rat kidney, and there have been no studies to our knowledge on renal MC4R expression in mice.…”
Section: Effect Of Hsd (4% Nacl) On Cardiovascular Function In Mc4r (mentioning
confidence: 95%
“…It also has protective effects in rat heart ischemia (Guarini et al 2002) and is involved in the anti-inflammatory effects of melanocortins in macrophages (Getting et al 2006). MC4R is expressed predominantly in the brain (Mountjoy et al 1994), although it was also detected in adipose tissue (Chhajlani 1996), in human skin melanocytes (Spencer & Schallreuter 2009), and in rat heart, lung, kidney, and testis (Mountjoy et al 2003). MC5R is widely found in peripheral tissue (Gantz et al 1994, Labbe et al 1994 and has also been detected in some areas of the CNS (Griffon et al 1994).…”
Section: Melanocortin Receptorsmentioning
confidence: 99%
“…The central melanocortin system appears to be an important mediator of the actions of both leptin and insulin (Seeley et al 1997, 2005, Williams et al 2001, Benoit et al 2002, which are key elements in the control of energy balance (Friedman 2002, Schneider et al 2002, Small et al 2002, Matsumura et al 2003, Mountjoy et al 2003, Pankov Iu 2005. Experimental blockade of melanocortin receptors (MCRs) in mice suppresses the ability of both leptin and insulin to reduce food intake and enhance weight loss (Benoit et al 2002, Seeley et al 2005.…”
Section: Introductionmentioning
confidence: 99%